Isolation of native Oncorhynchus mykiss bacteria with probiotic potential against Yersinia ruckeri - Quispe G., Wilson (2020)
The aim of this study was to identify native bacteria isolated from the intestinal tract of rainbow trout (Oncorhynchus mykiss) with probiotic properties against Yersinia ruckeri. In the study, 48 healthy trout from the hatchery of the Universidad Nacional del Altiplano (Puno, Peru) were used. The intestinal tract of the fry and juveniles was removed, and samples were taken from the intestinal mucosa. The samples were cultured on MRS agar and incubated at 30 °C for 24-48 h. The colonies were identified by their morphology and their inhibitory effect was evaluated in vitro against a Yersinia ruckeri strain isolated from a high mortality outbreak. Three isolates compatible with the genus Lactobacillus and one isolate compatible with the genus Bacillus were identified. These isolates showed inhibition halos greater than 9 mm in diameter against Y. ruckeri.